Efektivitas Pengelolaan Sampah Rumah Tangga Melalui Bank Sampah Kwt Mama Ceria di Nagari Pakandangan - Rahma, Fari; Jumiati, Jumiati (Indo-MathEdu Intellectuals Journal, 2025)
Littering household waste, burning, dumping into rivers and sewers. This has become a habit in some communities in Nagari Pakandangan. This practice encourages local community initiatives to manage household waste through the KWT Mama Ceria Waste Bank. This study aims to find out and analyze the effectiveness of household waste management through the Waste Bank in Nagari Pakandangan. This study uses a qualitative approach with a descriptive type of research. This research was conducted through field observation and in-depth interviews, as well as explicit documentation. Data analysis is carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawing. As a result, household waste management in Nagari Pakandangan has not been implemented optimally, but it is already on the right track in household waste management. Increasing the capacity of administrators in waste bank program management, recycling product marketing, and financial management will be very helpful in maximizing the potential of the KWT Mama Ceria Waste Bank